Optimalisasi Dosis Sodium Hypochlorite Pada Instalasi Pengolahan Air Perusahaan Umum Daerah di Kota X - Wildhan Muhammad Wiediyan; Wilma Nurrul Adzillah; Kania Ratnawati (Faculty of Engineering, Universitas Serambi Mekkah, 2024)
The water from Perumda must meet the current drinking water regulatory parameters, namely the Minister of Health Regulation No. 2 of 2023 on Drinking Water Quality Requirements. This research aims to test water parameters including temperature, pH, residual chlorine, E. coli, coliform and determine the optimum dose of disinfectant effort to eliminate E. coli and coliform bacteria in Perumda water in City X. The research method involves data analysis of water characteristic test results and laboratory scale experiments using 7 variations doses of sodium hypochlorite disinfectant ranging from 0.3 to 0.9 ppm. Research results show that temperature parameters can change because they are influenced by room temperature. pH parameter value increases with each additional dose of disinfectant with the highest value being 7.68. The residual chlorine parameter, a dose of 0.6 to 0.8 ppm, produces residual chlorine within the quality standard range, namely 0.2-0.5 mg/L. For E. coli and coliform parameters, a disinfectant dose of 0.6 to 0.9 ppm is able to reduce the E. coli and coliform content to the value of 0/100 mL. The conclusion of the research shows that the optimum dose for the elimination of E. coli and coliform bacteria is a dose of 0.6 ppm because it is able to eliminate bacteria with the lowest chlorine residue, namely 0.22 mg/L.